Creep properties of single crystal Ni-base superalloys (SX): A comparison between conventionally cast and additive manufactured CMSX-4 materials - Bürger, D.; Parsa, A. B.; Ramsperger, Markus; Körner, Carolin; Eggeler, G. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
The present work compares the microstructures and the creep properties of two types of single crystal Ni-base superalloy CMSX-4 materials (SXs). One was produced by conventional directional solidification Bridgman processing. The other was manufactured by selective electron beam melting (SEBM). The microstructures of the two types of materials are compared with emphasis placed on the large (dendritic/interdendritic regions) and small scale (γ-matrix/γ′-precipitates) microstructural heterogeneities, which characterize SX microstructures and their evolution during processing, heat treatment and creep. It is shown that heat treated SEBM materials have creep properties, which match or even outperform those of conventionally processed SX materials. Creep properties were assessed using a miniature creep test technique where [001] miniature tensile creep specimens were tested in the high temperature/low stress (1050 °C, 160 MPa) and in the low temperature/high stress (850 °C, 600 MPa) creep regimes. The creep behavior is interpreted based on microstructural results, which were obtained using analytical scanning and transmission electron microscopy (SEM and TEM).
CRIS-Team Scopus Importer:2019-07-12
Keywords: Additive manufactured single crystal; Creep; Directionally solidified single crystals; Microstructure; Ni-base single crystal superalloys